Size distribution and rate of dust generated during grain elevator handling - Boac, Josephine M.; Maghirang, Ronaldo G.; Casada, Mark E.; Wilson, Jeff D.; Jung, Yoon‐Sung (My University, 2009)
Dust generated during grain handling can pose a safety and health hazard and is an air pollutant. This study was conducted to characterize the particle size distribution (PSD) of dust generated during handling of wheat and shelled corn in the research elevator of the USDA Grain Marketing and Production Research Center and determine the effects of grain lot, repeated transfer, and grain types on the PSD. Dust samples were collected on glass fiber filters with high volume samplers from the lower and upper ducts upstream of the cyclone dust collectors. A laser diffraction analyzer was used to measure the PSD of the collected dust. For wheat, the size distribution of dust from the upper and lower ducts showed similar trends among grain lots but differed between the two ducts. The percentages of particulate matter (PM)‐2.5, PM‐4, and PM‐10 were 5.15%, 9.65%, and 33.6% of the total wheat dust, respectively. The total dust mass flow rate was 0.94 g/s (equivalent to 64.6 g/t of wheat handled). For shelled corn, the size distributions of the dust samples from the upper and lower ducts also showed similar trends among transfers but differed between the two ducts. The percentages of PM‐2.5, PM‐4, and PM‐10 were 7.46%, 9.99%, and 28.9% of the total shelled corn dust, respectively. The total dust mass flow rate was 2.91 g/s (equivalent to 185.1 g/t of corn handled). Overall, the corn and wheat differed significantly in the size distribution and the rate of total dust generated.
Keywords: Grain elevator; Particle size distribution; Geometric mean diameter; Isokinetic sampling; Dust mass flow rate; Particulate matter